The interplay of production commercialisation and specialization: An empirical study on Chinese smallholders - Li, Lihua; Varua, Maria Estela; Komarek, Adam M.; Shankar, Sriram; Bellotti, William D. (Emerald Publishing Limited, 2017)
The purpose of this paper is to explore the endogenous relationship between production specialisation and market commercialisation with an empirical study of farmers in Northwest China.The three-stage least squares were used to address simultaneity and over-identification problems in comparison with two-stage least squares (2SLS). The Durbin-Wu-Hausman test was employed to identify the endogeneity of the commercialisation and specialisation variables. The validity, relevance, and strength of the instruments were tested using the Stock-Yogo weak instrument diagnostics test.A two-way interrelationship between specialisation and commercialisation were confirmed, and suggest that farmers’ decisions on farm commercialisation and production specialisation are actually separate and interacting.By demonstrating that a virtuous cycle exists between agricultural commercialisation and on-farm specialisation, policies can be formulated to complement these two effects that may help increase small holders’ income. Farmers’ market participation can be indirectly improved by combining market improvement and risk management tools to encourage production specialisation.The insights of this study cast further light onto the farm market participation theory by emphasising that higher asset endowments enable small farmers to specialise in production with comparative advantage.